(untitled) (Revista de Ciências Agroveterinárias, 2011)
In order to evaluate renal function of broiler chickens experimentally intoxicated with sub-acute dose of afl atoxins in the diet, in interaction with vaccination and viral challenge with subclinical strain of infectious bursal disease (IBD), weekly dosages of serum protein, albumin, non-protein nitrogen (uric acid, urea and creatinine) and the minerals calcium and phosphorus were performed in poultry divided into five groups. Each group received one of the following treatments: Group A (control): birds received no challenge or vaccination against DIB, with ration free of aflatoxins in general; Group B (only afl atoxins): birds received no challenge or vaccination against DIB and fed with contaminated ration with 1.25 ppm of afl atoxins in the first 42 days of life; Group C (only vaccination): birds only vaccinated against the DIB in the first and twelfth days of life, with diet free of aflatoxins, and without viral challenge; Group D (challenge): birds only challenged for DIB on the fourteenth day of life with fi eld strain of a subclinical DIB, without vaccinations, and diet free of aflatoxins; Group E (interaction): birds vaccinated for DIB in the fi rst and twelfth days of life, receiving ration contaminated with 1.25 ppm of aflatoxins, and the same viral challenge of Group D. Levels of urea and creatinine presented no significant differences among the different treatments. However, there was an increase in uric acid levels four days after viral challenge, followed by hyperphosphatemia after 14 days, and hypercalcemia after 21 days until the end of the experiment. In Group B (only aflatoxins), a hypophosphatemia was observed at 18 days of age. The use of commercial vaccines according to the manufacturer’s instructions and practices routinely carried out by the poultry industry are effective against the viral action on the renal system, promoting a protective effect. This fact was demonstrated by the results obtained by laboratory tests.